Educação permanente para implantação de Programa de Promoção da Alimentação Adequada e Saudável: perspectiva do gestor e dos profissionais de saúde - Rayane Jeniffer Rodrigues Marques (2018)
Introduction: The Unified Health System has a fundamental role in the reorientation of health education strategies in Brazil. Historically, he has proposed changes in ways of teaching and learning in different sectors. Objectives: To analyze, from the perspective of the manager and professionals of Primary Health Care (ABS), the activity of permanent education (PE) proposed for implementation of the Program of Promotion of Adequate and Healthy Food Promotion (PAAS), as well as methodology proposed by the Program. Methods: A qualitative study was conducted with the manager and professionals of the Family Health Support Center and the Family Health Strategy of the municipality of Nova Lima, Minas Gerais. Interviews were conducted with semi-structured script, which were later transcribed and analyzed by the thematic content analysis technique. Results: This dissertation will be presented in two articles: 1) "Permanent Education aimed at promoting adequate and healthy food in Primary Health Care: manager and health professionals' perspective"; 2) "Working with groups in Primary Health Care: a new methodological proposal focused on promoting adequate and healthy food". It was verified, in the first article, the insufficient accomplishment of PE activities in the municipality, most of the activities reported by the professionals are courses, punctual qualifications, meetings with vertical characteristics and little problematizing. There was also little space for the construction of knowledge and the exchange of knowledge in daily work. In this context, the EP for the implementation of the PAAS Program was important for promoting reflection on the practice. Its novelty, in the face of what has been experienced by health professionals, seems to have made it possible to raise awareness, including the manager, for the analysis of the work process. In the second article, it was observed that the experiences of group work developed by the professionals seemed ineffective due to several factors, especially poor planning, the educational strategies used and the integration of the team. The predominance of methodologies based on the transmission of knowledge as lectures did not favor the construction of knowledge, as well as the adhesion of users and professionals to the collective approach. On the other hand, the linking of the groups to the renewal of revenues and the adoption of other attractions were not sufficient to increase the participation in the groups. The development of effective groups with good adherence in ABS requires the combination of different strategies based on scientific evidence and participatory methodologies. Thus, the methodology of group work proposed by the PAAS Program seemed to fill a gap existing in the municipality for the planning of collective actions, and it is even possible to be used, according to the professionals, in groups that deal with other issues and other professionals who are not nutritionists. Conclusion: The insufficient performance of EP activities in the municipality was highlighted by the professionals, mainly focused on food and nutrition, and their distancing with the assumptions of the National Policy of EP, although there is a specific sector for this. Most of the reported activities were with vertical characteristics and little problematization, despite the interest of some professionals for PE activities with problematizing approaches. In addition, there was little space for the construction of knowledge and the exchange of knowledge in the daily work, a profile that is compatible with the reality of other municipalities, therefore, potential public to participate in PE actions aimed at PAAS. Thus, PE activity proved to be effective in promoting the professionals' reflection on their practice and the possible improvements in the conduction of health promotion groups in ABS. In addition, it appeared to fill a gap in the municipality with regard to EP focused on group methodology. The experiences of group work developed by professionals seemed ineffective due to several factors, the predominance of methodologies based on the transmission of knowledge as lectures, did not favor the construction of knowledge, as well as the adhesion of users and professionals to the collective approach. The group methodology, proposed by the PAAS Program and addressed in the PE activity, seemed to the professionals to be able to assist them in the conduction of groups focused on the valorization of the subject, exchange of knowledge, empowerment and the construction of autonomy. This was made possible by the combination of different strategies based on scientific evidence and participatory methodologies such as dialogue, problem-solving and reflection, which could impact on positive changes in individuals' health and the building of bonds, fundamental elements for effectiveness and good adherence groups in ABS. Thus, the Instruction that conveys the group methodology, as well as the subsidiary materials, proposed by the Ministry of Health are innovative because it contains all the planning of collective actions, and is even possible to be used in groups that deal with other issues and professionals other than nutritionists. In addition, it favored strengthening and confidence in itself and in the team, contributing to generate reflection and the desire to change the work process. These results were probably achieved due to the approach used as the guiding principle of the group methodology and the EP activity for its implementation to be the problematizing methodology articulated with other educational theories. In addition, the possibility of its development by interdisciplinary team and flexibility according to the routine of service are other characteristics that strengthen its application in ABS aiming at the improvement of the actions of health promotion. It is believed that the results found have the potential to reflect on the operationalization of the PE Policy, with the possibility of developing effective strategies that will improve PAAS actions in the municipality.